Jill's new bike: stories and poems - Hunt, Roderick; Parkins, David Shannon, Kate (Oxford University Press London, 1987)
"Jill's New Bike" by Roderick Hunt is a delightful collection of stories and poems centered around Jill and her adventures with her new bicycle. Through various engaging tales, Jill explores her surroundings, learns about friendship, and faces challenges that come with riding her bike. The stories emphasize themes of discovery, resilience, and the joy of cycling, making it a fun read for children. With vibrant illustrations and relatable characters, the book encourages young readers to embrace adventure and enjoy the outdoors.